2006
DOI: 10.1523/jneurosci.3898-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Human Dorsal Premotor Cortex Generates On-Line Error Corrections during Sensorimotor Adaptation

Abstract: A number of different sites in the human brain have been shown to play a role in sensorimotor adaptation. However, the specific role played by each of these structures in the learning process is poorly understood. In the present study, the contribution of the dorsal aspect of the premotor cortex was examined by disrupting activity at this site using transcranial magnetic stimulation (TMS) while subjects wearing prism goggles pointed at visual targets. This manipulation slowed down the rate of adaptation when v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
55
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 29 publications
2
55
1
Order By: Relevance
“…Transient inactivation of the premotor cortex with transcranial magnetic stimulation results in a reduction of visually dependent online corrections of reaching during sensorimotor adaptation (Lee and van Donkelaar, 2006), while interfering with parietal activity compromises the trajectory adjustments necessary to move in a novel dynamic force field (Della-Maggiore et al, 2004). Furthermore, parietal lesion can result in delayed and impaired trajectory corrections when a sudden shift of target location occurs (Pisella et al, 2000;Gréa et al, 2002;BattagliaMayer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Transient inactivation of the premotor cortex with transcranial magnetic stimulation results in a reduction of visually dependent online corrections of reaching during sensorimotor adaptation (Lee and van Donkelaar, 2006), while interfering with parietal activity compromises the trajectory adjustments necessary to move in a novel dynamic force field (Della-Maggiore et al, 2004). Furthermore, parietal lesion can result in delayed and impaired trajectory corrections when a sudden shift of target location occurs (Pisella et al, 2000;Gréa et al, 2002;BattagliaMayer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, humans learn to navigate a new route as a series of turns (egocentric co-ordinates) plus as a series of key landmarks within the landscape (allocentric co-ordinates, (Vidal et al 2004)). Similarly, learning to make reaching movements within a visually distorted environment requires changes within egocentric plus allocentric co-ordinates (Hatada et al 2006; Lee and van Donkelaar 2006). Improved performance during learning is supported by the encoding of skill within both co-ordinate frames.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in separate training sessions, they applied single-pulse transcranial magnetic stimulation (TMS) to the PMd either at the onset or termination of the movement. Lee and van Donkelaar (2006) report that TMS at the onset of a movement disrupted both on-line error corrections and sensorimotor adaptation, whereas a pulse at termination had no effect [Lee and van Donkelaar, their Comparison of preadaptation and postadaptation performance on specialized tests revealed that sensorimotor adaptation could not be attributed to a remapping of the visuospatial environment, but rather, was attributable to adaptation of proprioceptive information [Lee and van Donkelaar, their The PMd could have a direct or indirect role in adaptation: indirectly via its necessity for the on-line corrections that are required for sensorimotor adaptation, or directly by subserving both adaptation and correction.…”
mentioning
confidence: 99%
“…For example, interactions between PMd and the cerebellum may be critical to sensorimotor adaptation because trial-by-trial adaptation requires cerebellar processing (Martin et al, 1996). The results reported by Lee and van Donkelaar (2006) could reflect disrupted implementation or translation of critical cerebellar contributions to sensorimotor adaptation. If PMd played a direct role in sensorimotor adaptation, TMS should have impaired adaptation in the terminal vision condition, which best approximates the task used previously by Martin et al (1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation